Optimization of the Esterification Process of Crude Palm Oil (CPO) with Natural Zeolite Catalyst Using Response Surface Methodology (RSM) - Fadhilah, Said Ahmad; Fatkhurin, Elma; Sari, Ni Ketut (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Esterification is one of the important processes in the production of biodiesel. This is done to ensure that the FFA content in CPO is less than 3%. The esterification reaction can be accelerated by using natural zeolite as a catalyst. Optimization needs to be carried out to select the appropriate conditions to reach the optimal region quickly. The purposes of this research are to analyze the impact of esterification time and the natural zeolite catalyst size on the reduction of FFA levels and find the optimal parameters in the CPO esterification through RSM. Esterification is operated by maintaining the reaction temperature at 60 °C, agitation speed at 150 rpm, and using a molar ratio of methanol:CPO of 6:1. The independent variables used in the research are esterification time (90, 110, 130, 150, and 170 minutes) and natural zeolite size (20, 40, 60, 80, and 100 mesh). The optimization results using RSM indicate that the optimum points in the study are at an esterification time of 170 minutes and a natural zeolite size of 97.3909 mesh.